Perancangan Plat Beton Bertulang Lantai Kendaraan Jembatan dengan Program Komputer. - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Kehutanan Universitas Gajah Mada, 1999)
ABSTRAK This paper discusses the use of computer program for designing the Hoof slab of highway bridge using the M.Pigeaud method. The approximate value of moment coeffcient was acknowledged by using Fourier series, which is also used in the Navier method. The result shows a validation of 6,7 % and its leads to a conclusion that this computer program is proper to be used. Key word: Plat beton bertulang, program komputer, jembatan